Controlled growth of Cu and CuOx thin films from subvalent copper precursors. Issue 38 (17th September 2020) - Jürgensen, Lasse; Höll, David; Frank, Michael; Ludwig, Tim; Graf, David; Schmidt-Verma, Anna Katrin; Raauf, Aida; Gessner, Isabel; Mathur, Sanjay
Abstract : Volatile mixed-ligand complexes of copper based on stabilizing cyclooctadiene and reactive enaminone are reported as efficient precursors for chemical vapor deposition of Cu(0), Cu2 O, or CuO thin films. Abstract : A new Cu(i ) precursor, [(COD)Cu(TFB-TFEA)] (COD = 1, 5-cyclooctadiene and TFB-TFEA = N -(4, 4, 4-trifluorobut-1-en-3-on)-6, 6, 6-trifluoroethylamine) with high volatility and a clean thermal decomposition pattern was tested for thermal and plasma-assisted chemical vapor deposition (CVD). The heteroleptic configuration based on an anionic and a chelating neutral ligand unified both reactivity and sufficient stability resulting in an intrinsic molecular control over the composition of the resulting CVD deposits. The electronic influence of the ligand on the metal site was studied by 1D and 2D NMR spectroscopy, while EI mass spectrometry revealed the ligand elimination cascade. Thermal and plasma CVD experiments demonstrated the suitability of the copper compound for an atom-efficient (high molecule-to-material yield) deposition of copper(0) and copper(i ) oxide films that could be converted into crystalline copper(ii ) oxide upon heat treatment at 500 °C.